Energy Efficient Homes: Home Inspections - Kathleen C. Ruppert; Anna Cam Fentriss; Hyun-Jeong Lee (EDIS)
FCS-3279, a 3-page fact sheet by Kathleen C. Ruppert, Anna Cam Fentriss, and Hyun-Jeong Lee, answers home buyers’ questions about how to choose a home inspector, Home Energy Ratings, and mold and fungus inspections. It is one of an Energy Efficient Homes series. Published by the UF Department of Family Youth and Community Sciences, June 2008.